The Prevalence of Epilepsy and Association With Traumatic Brain Injury in Veterans of the Afghanistan and Iraq Wars. Issue 1 (January 2015) - Pugh, Mary Jo V.; Orman, Jean A.; Jaramillo, Carlos A.; Salinsky, Martin C.; Eapen, Blessen C.; Towne, Alan R.; Amuan, Megan E.; Roman, Gustavo; McNamee, Shane D.; Kent, Thomas A.; McMillan, Katharine K.; Hamid, Hamada; et al.
<x xml:space="preserve">Abstract</x> Objective: To examine the association of epilepsy with traumatic brain injury (TBI) in Afghanistan and Iraq (Operation Enduring Freedom [OEF]/Operation Iraqi Freedom [OIF]) Veterans. Design: Cross-sectional observational study. Participants: A total 256 284 OEF/OIF Veterans who received inpatient and outpatient care in the Veterans Health Administration in fiscal years 2009-2010. Main Outcome Measures: We used algorithms developed for use with International Classification of Diseases, Ninth Revision, Clinical Modification, codes to identify epilepsy, TBI (penetrating TBI [pTBI]/other TBI), and other risk factors for epilepsy (eg, stroke). TBI and other risk factors were identified prior to the index date (first date of seizure or October 1, 2009) for primary analyses. Results: Epilepsy prevalence was 10.6 per 1000 (N = 2719) in fiscal year 2010; age-adjusted prevalence was 6.1. Of 37 718 individuals with a diagnosis of TBI, 29 297 Veterans had a diagnosis of TBI prior to the index date. Statistically significant associations were found between epilepsy and prior TBI diagnosis (pTBI: adjusted odds ratio = 18.77 [95% confidence interval, 9.21-38.23]; other TBI: adjusted odds ratio = 1.64 [1.43–1.89]). Conclusions: Among OEF/OIF Veterans, epilepsy was associated with previous TBI diagnosis, with pTBI having the strongest association. Because war-related epilepsy in Vietnam War Veterans with TBI continued 35 years postwar, a detailed, prospective study is needed to understand the relationship between epilepsy and TBI severity in OEF/OIF Veterans.